Integrating HIV pre‐exposure prophylaxis and harm reduction among men who have sex with men and transgender women to address intersecting harms associated with stimulant use: a modelling study. (19th June 2020) - Bórquez, Annick; Rich, Katherine; Farrell, Michael; Degenhardt, Louisa; McKetin, Rebecca; Tran, Lucy T.; Cepeda, Javier; Silva‐Santisteban, Alfonso; Konda, Kelika; Cáceres, Carlos F.; Kelly, Sherrie; Altice, Frederick L.; et al.
Abstract: Introduction: Among men who have sex with men (MSM) and transgender women (TW), stimulant use is high and has been associated with an increased risk of HIV infection, suicide and cardiovascular disease (CVD) mortality. We used epidemic modelling to investigate these intersecting health harms among MSM/TW in Lima, Peru and assess whether they could be mitigated by prioritizing HIV pre‐exposure prophylaxis (PrEP) and harm reduction interventions among MSM/TW who use stimulants. Methods: We adapted a dynamic model of HIV transmission among MSM/TW in Lima to incorporate stimulant use and increased HIV risk, suicide and CVD mortality. Among 6% to 24% of MSM/TW using stimulants (mostly cocaine), we modelled an increased risk of unprotected anal sex (RR = 1.35 [95%CI: 1.17 to 1.57]) obtained from local data, and increased risk of suicide (SMR = 6.26 [95%CI: 2.84 to 13.80]) and CVD (SMR = 1.83 [95%CI: 0.39 to 8.57]) mortality associated with cocaine use based on a global systematic review. We estimated the proportion of health harms occurring among MSM/TW who use stimulants in the next year (01‐2020/01‐2021). We also investigated the 10‐year impact (01‐2020/01‐2030) of: (1) PrEP prioritization for stimulant‐using MSM/TW compared to random allocation, and (2) integrating PrEP with a theoretical intervention halving stimulant‐associated risk. Results: MSM/TW in Lima will experience high HIV incidence, suicide mortality and CVD mortality (1.6/100 py, and 0.018/100 py, 0.13/100 py respectively) in 2020. Despite stimulant using MSM/TW comprising an estimated 9.5% (95%CI: 7.8 to 11.5) of all MSM/TW, in the next year, 11% 95%CI (i.e. 2.5% to 97.5% percentile) 10% to 13%) of new HIV infections, 39% (95%CI: 18% to 60%) of suicides and 15% (95%CI: 3% to 44%) of CVD deaths could occur among this group. Scaling up PrEP among all stimulant using MSM/TW could prevent 19% (95%CI: 11% to 31%) more HIV infections over 10 years compared to random allocation. Integrating PrEP and an intervention to halve stimulant‐associated risks could reduce new HIV infections by 20% (95%CI: 10% to 37%), suicide deaths by 14% (95%CI: 5% to 27%) and CVD deaths by 3% (95%CI: 0% to 16%) over a decade. Conclusions: MSM/TW who use stimulants experience a disproportionate burden of health harms. Prioritizing PrEP based on stimulant use, in addition to sexual behaviour/gender identity criteria, could increase its impact. Integrated substance use, harm reduction, mental health and HIV care among MSM/TW is needed.